Efficiency of scattering algorithm with overset grid generation for detection of buried object - Deanne, anak Edwin; Shafrida, binti Sahrani; Kismet, anak Hong Ping (Institute of Electrical and Electronics Engineers Inc., 2018)
The safety of building and civil structures affected by seismic waves emanating from the earthquakes has always been of concern to the general public. Post-hazard assessments must be conducted to ensure the integrity of the affected buildings, infrastructures and lands before continuing usage. Extensive research on damage detection of buildings and civil structures has recently been performed. However, it remains a significant problem and yields an unpredictable outcome as in most cases the results from a certain method applied to one structure are not valid for other structures. The Forward-Backward Time-Stepping (FBTS) technique utilizing Finite-Difference Time-Domain (FDTD) method and Overset Grid Generation (OGG) method is proposed to solve the problem. This paper investigates the accuracy of the proposed method by the analysis with various ratio of grid size between the main mesh and sub mesh. The signal analysis is carried out for inverse scattering with empty grid that overlapped on the main mesh. It is shown that the smaller grids give more accuracy for the results. © 2017 IEEE.